Aliran Klasisme dalam Sastra Arab‎ Modern: Dasar Pemikiran, Karakteristik, ‎Pelopor dan Kritik - Umam, Muhammad Choirul Umam; Amrullah, Friendis Syani (Jurnal Al-Maqoyis, 2025)
Arabic literature in the modern era has undergone continuous development, giving rise to literary schools of thought, the first of which was the classical school. This research aims to reveal the classical school in modern Arabic literature from the perspective of its fundamental thoughts, characteristics, pioneer, and criticism. The research was library research with a descriptive approach. The data collection method used was documentation through reading and writing. Data analysis was based on a four-step classification analysis method, namely reduction, classification, composition, and interpretation or explanation. The results of the research indicate that 1) The basis of the idea for the emergence of the classical school in modern Arabic literature is a response to the emergence of the classical school in the West and a reaction to the influence of Western culture and literature on Arabic literature. 2) The characteristics of the classical school in modern Arabic literature are thematic, containing human values, prioritising logic in the creation of literary works, using ancient poetic styles, and using facts as inspiration. 3) The pioneer of the classical school in modern Arabic literature is Mahmoud Sami Pasha, son of Hassan Husni al-Baroudi, known as the Lord of the Sword and the Pen, Prince of Poets and Poet of Princes. 4) Criticism of the classical school in modern Arabic literature came from the perspective of Islam, because the classical school is closely linked to Greek and Roman literature, which are pagan in spirit, It neglects social and political problems in favour of principles related to the view of worldly and otherworldly life, favours a particular social group, and attributes human and moral values to a particular time and place, both of which are changeable.